Giving ourselves the edge: capitalising on collaboration - Jill Hanson; Alison Pope; Carolina Salinas (Journal of Learning Development in Higher Education)
This paper considers the collaboration of academics and third-space professionals to create an enrichment programme in an English university. It briefly outlines the programme and explores student engagement and reaction to it before identifying tentative short-term outcomes associated with it: increases in self-reported self-confidence, academic, digital, professional, and leadership skills. The programme created space and time for academics and third-space professionals to come together, share their knowledge, and recognise each other’s expertise to manifest ‘knotworking’ (Veles, 2022). A project lead with experience of being an academic and a third-space professional helped to facilitate understanding and develop ‘ingroup’ features such as a sense of shared connection, co-operation, mutual help, and respect for each other. We conclude that an evolving framework of third-space professionals which is firmly part of the real institutional fabric leads to less reliance on project-based reinventions and instead fosters a steady rate of beneficial progress for the entire learning community.